농촌주민의 외지인 농촌이주에 대한 태도 분석 - 황정임 (한국농촌경제연구원, 2013)
Recent research on rural in-migration has mostly been done from an in-migrants' perspective. This paper, however, centers on rural residents' attitudes toward in-migrants from outside. Rural residents' attitudes are important because they can significantly affect the success or failure of in-migrants' settling in rural areas. Analysis is conducted using data from Survey on Rural Living Indicators. Results indicate that key predictors of rural residents' attitudes toward in-migrants are engagement in agriculture, satisfaction with community environment and a sense of community.
Keywords: 농촌 이주; 이주민에 대한 태도; 순서형 프로빗 모형; rural in-migration; attitudes towards immigrants; ordered probit model